Finite-Time Adaptive Control for a Class of Nonlinear Systems With Nonstrict Feedback Structure - Sun, Yumei; Chen, Bing; Lin, Chong; Wang, Honghong (IEEE transactions on cybernetics, 2018)
This paper focuses on finite-time adaptive neural tracking control for nonlinear systems in nonstrict feedback form. A semiglobal finite-time practical stability criterion is first proposed. Correspondingly, the finite-time adaptive neural control strategy is given by using this criterion. Unlike the existing results on adaptive neural/fuzzy control, the proposed adaptive neural controller guarantees that the tracking error converges to a sufficiently small domain around the origin in finite time, and other closed-loop signals are bounded. At last, two examples are used to test the validity of our results.